Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Reconstruction and projection of the evolution of Schiaparelli Glacier, Southern Patagonia (1749–2100) using OGGM constrained by dendroglaciological records - Yafan Hu; Ru Huang; Haifeng Zhu; Xiaolong Zhu; Jussi Grießinger; Eryuan Liang; David Farías-Barahona; Ilaria Tabone; Wolfgang Jens-Henrik Meier (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rationally designed aluminum-supported g-C3N4: An efficient and halogen-free catalyst for CO2-epoxide cycloaddition - Man Zhao; Wen-Jun Xie; Shan-Shan Chen; Hong-Ru Li; Liang-Nian He (Journal of Environmental Chemical Engineering, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Asymmetric evolution of capturability of atmospheric water (CAW) across global arid and humid regions - Hou-Liang Lu; Hong-Ru Wang; Hui-Min Zuo; Han Zhou; Yu-Fei Jiao; Bill X. Hu (Journal of Hydrology, 2026)

Construction of Brick-Wall-Like Topological Olefin-Linked Covalent Organic Frameworks via a Steric-Hindrance-Mediated Strategy for Efficient Uranium Capture - Cheng-Peng Niu; Rui Zhang; Zhi-Hai Peng; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2026)

Microbial and metabolomic analyses elucidate the Debaryomyces hansenii-mediated flavor enhancement in dry-aged black pig pork - Ruo-Chun Kao; Meng-Ru Lee; Rung-Jen Tu; Wen-Shyan Chen; Hsiao-Mei Liang; Hsiu-Ming Liu; Hsin-Hui Su; Yen-Po Chen; Yung-Tsung Chen (Food Microbiology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Facial width-to-height ratio predicts aggression and contest outcomes in wild golden snub-nosed monkeys - Pei Zhang; Yan-Ni La; Fei Niu; Jin-Bang Zhang; Paul A. Garber; Derek W. Dunn; Ru-Liang Pan; Kang Huang; Bao-Guo Li (Animal Behaviour, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Stable leaf pH of grassland community under nitrogen inputs ensured by contrasting intra- and inter-specific variations - Xiao-Hua Yang; Cong Ding; Xiao-Sa Liang; Yuan-Xiu Wu; Xiao-Ru Zhang; Xiao-Jing Zhang; Liang-Chao Jiang; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Triazine herbicide prometryn impaired trophic link between phytoplankton and zooplankton Brachionus plicatilis by diminishing polyunsaturated fatty acids contents - Wei Liang; Yilei Li; Ziang Zhao; Dongchu Zhao; Yue Wang; Liqiang Yang; Shaoguo Ru; Xiaona Zhang (Marine Pollution Bulletin, 2026)

Comprehensive metabolic programming by enzymatic nanovesicle for acute kidney injury therapy - Yao Lei; Yuzhu Wu; Chao Li; Canwei Zou; Mingchuan Mao; Wan-Ru Zhuang; Yun Qu; Jiaqi He; Chao Liang; Weidong Nie; Hai-Yan Xie (Science Bulletin, 2026)

Intensified drought and vegetation-specific responses in the Tianshan Mountains, Central Asia - Huaijun Wang; Yaning Chen; Liang Ren; Zhi Li; Ru Feng; Zhiguo Ren; Yuanqiao Li; Yaxue Yang; Yingping Pan (CATENA, 2026)

Water use complementarity in old-growth mixed forests versus competition in younger successional mixed forests - Ru Huang; Wolfgang Jens-Henrik Meier; Achim Bräuning; Peili Fu; Zexin Fan; Sugam Aryal; Mohsen Arsalani; Haifeng Zhu; Chenxi Xu; Eryuan Liang; Shalik Ram Sigdel; Jussi Grießinger (Agricultural and Forest Meteorology, 2026)

Mechanisms of flow-induced noise and control in underwater grille-cavity systems: Effects of grille number and inclination - Qing-Shuang Zhang; Yong-Liang Xiong; Ru-Nan Hua; Guo-Cang Sun; Dan Yang (Ocean Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Integrative morphological and genomic analyses reveal diversity, reticulate evolution, and adaptation in diploid and tetraploid Rosa species from Xinjiang - Zhongyu Tang; Zhenlong Liang; Hengning Deng; Liangying Li; Jian Ru; Shiqi Li; Jia Miao; Cheng Zhang; Xinfen Gao (Molecular Phylogenetics and Evolution, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Rational design of one-dimensional chain-like metal-organic frameworks featuring engineered nano-pockets for highly selective and efficient uranium sequestration - Zhi Wu; Shu-Yuan Zhang; Bin Lin; An-Min Song; Fei-Yi Kong; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

Enantioselective photoenolization/Diels–Alder reaction catalyzed by chiral Brønsted acid - Bin-Xian Chen; Xiang-Kui He; Bao-Ru Yuan; Liang-Qiu Lu; Ying Cheng; Wen-Jing Xiao (Science Bulletin, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Sand flux patterns derived from static morphology and migration behavior of barchan dunes in the Taklamakan Desert - Yuan Wang; Peng Liang; Xiaoping Yang; Jiwei Wu; Tinglin Ru; Zihan Wu (Geomorphology, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Artificial restoration improved the complexity of the soil microbial co-occurrence network and the resistance of microbial communities to environmental changes in degraded sandy grassland - Wentao Mi; Ru Meng; Weibo Ren; Ting Yuan; Yi Liu; Huijie Han; Jialu Liang; Jinqi Zhang (Agriculture, Ecosystems & Environment, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Aging enhancement and synergistic effect on toxicity to soil fauna by polystyrene microplastics-tetrabromobisphenol A toxicity exposure - Jianning Chang; Haibo Zhang; Jinsong Liang; Guangming Zhang; Yajie Zhang; Ru Zhang; Maoqing Wang; Su Shiung Lam; Shaoqing Guo; Panyue Zhang (Environmental Research, 2026)

Effect of environmentally relevant concentrations of estrogens on the fear-like response of male zebrafish - Ying-Ying Zhang; Ru-Yi Tan; Hong Tao; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Built-in electric field and surface adsorption enhanced gas detection of muti-interface MXene/TiO2/Bi2MoO6 integrated heterostructure - Yan Liang; Peipei Yan; Xiaojian Zhao; Chunbo Ru; Lu Tang; Yu Jiang; Yong Yang (Chemical Engineering Journal, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

ZnCl2 activated biochar and chitosan composites for efficient adsorption of tetracycline pollution in sewage - Chi Ru; Xixi Lian; Dong Liang; Taoli Huhe; Rui Shan; Haoran Yuan; Yong Chen (Process Safety and Environmental Protection, 2025)

Potentials of food-derived peptides as novel antihypertensive agents and their acting mechanisms - Ru-Xue Guo; Liang Shen (Food Chemistry, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

The cotton gene family encoding translationally controlled tumor proteins and the role of GhTCTP5 in salt tolerance - Bo Pang; Jialin Chen; Ping Luo; Ru Zhang; Jing Li; Weiwei Liang; Wenwei Gao; Shengmei Li (Plant Science, 2025)

Enrichment of Feammox microflora utilizing in-situ iron in excess activated sludge: substrate metabolism, gene variation, and microbial communities - Maoxia Chen; Jing Ru; Yan Yi; Yang Li; Liang Wu; Huiling Jiang (Bioresource Technology, 2025)

Multi-omics decodes exercise-induced geroprotection: betaine unlocks aging delay via TBK1 inhibition - Yang Li; Liang Guo; Ru Wang (Science China Life Sciences, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Atmospheric microplastic deposition in Guilin karst wetlands: Sources and agricultural impact - Lishan Zhang; Bihong Xu; Zengxian Wei; Xiaolu Liang; Yan Chen; Xuan Ru; Qian Zhang; Shan Zhong (Atmospheric Pollution Research, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Indoor and outdoor bioaerosol distributions and concentration profiles during different seasons and pollution events in Qingdao city - Ru Zhao; Liang Guo; Jianhua Qi; Taicheng An (Building and Environment, 2025)

The Astrocyte: A New Component of The Engram Regulates Memory Recall - Ru Li; Zilan Luo; Ding Zhong; Xia Deng; Liang Gao (Neuroscience Bulletin, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

How does digital industry agglomeration drive carbon peaking and carbon neutrality in China? The role of digital technology innovation - Ru-Yu Xu; Ke-Liang Wang (Journal of Cleaner Production, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Toxicity and Safety Assessment of Key Pesticides Used in Rice Fields on Rice Flower Carp (Procypris merus) - Qianxue Shao; Yongming Ruan; Ru Liang; Ruixin Jin; Zhixi Jin; Lin Xie; Yongqing Chi; Jiaojiao Xia; Pingyang Zhu (Fishes, 2025)
Integrated rice–fish farming, crucial for sustainable agriculture, relies on the judicious use of pesticide. This study evaluates the toxicity of six common rice-field pesticides on Procypris merus (rice flower carp), a key species in these systems. We conducted acute and chronic toxicity tests, assessing survival, growth, oxidative stress (SOD, CAT, MDA, 8-OHdG), and neurotoxicity (AChE). Results revealed a spectrum of toxicity: abamectin and trifloxystrobin were highly toxic; pretilachlor was moderately so; and glufosinate-ammonium, triflumezopyrim, and thiazole zinc were low. Notably, triflumezopyrim induced significant oxidative stress and DNA damage, while all three low-toxicity pesticides inhibited AChE activity, indicating potential neurotoxicity. Despite these effects, all observed toxicities were reversible within 7–14 days. Considering that the tested concentrations exceeded typical field application rates, glufosinate-ammonium, triflumezopyrim, and thiazole zinc are deemed relatively safe for P. merus at recommended dosages. Our findings provide critical insights for optimizing pesticide selection in rice–fish farming, balancing pest control with ecological safety, thereby informing sustainable agricultural practices.

A late summer temperature reconstruction based on tree-ring maximum latewood density since AD 1246 on the southeastern Tibetan Plateau - Ru Huang; Hong Yin; Haifeng Zhu; Eryuan Liang; Atta Ullah; Wolfgang Jens-Henrik Meier; Fayaz Asad; Achim Bräuning; Jussi Grießinger (Quaternary Science Reviews, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

SERS-ATB: A comprehensive database server for antibiotic SERS spectral visualization and deep-learning identification - Quan Yuan; Jia-Wei Tang; Jie Chen; Yi-Wen Liao; Wen-Wen Zhang; Xin-Ru Wen; Xin Liu; Hui-Jin Chen; Liang Wang (Environmental Pollution, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Performances and mechanisms of granular activated carbon enhancing n-caproate production via chain elongation - Ru Zhang; Wei Fang; Qingyan Wang; Ziyi Fang; Jinsong Liang; Le Chen; Jianning Chang; Yajie Zhang; Wenjing Yang; Panyue Zhang; Guangming Zhang (Journal of Environmental Management, 2025)

The effects of water flow velocity and odor release frequency on the odor-tracking behavior of swimming crabs (Portunus trituberculatus) - Ru Wang; Xin Wang; Qihang Liang; Teng Jiang; Liang Yue; Fang Wang; Dapeng Liu (Aquaculture, 2025)

A strategy for the quality control in Polyrhachis dives: Identification and quantification of specific peptides using untargeted and targeted mass spectrometry approaches - Xialin Chen; Dandan Li; Rongrong He; Jiajia Wang; Ru Yang; Mengyu Qian; Liang Cao; Yongwen Zhang; Zhenzhong Wang; Wei Xiao (Food Research International, 2025)

Fast simulation strategy for capacitively-coupled plasmas based on fluid model - Jing-Ze Li; Ming-Liang Zhao; Yu-Ru Zhang; Fei Gao; You-Nian Wang (Computer Physics Communications, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Ultra-low energy wastewater remediation: Excellent properties of smart adsorption membranes - Yun-Hao Xia; Ying-Ying Gui; Jia-Hua Zhou; Gui-E Chen; Zhe-Ru Shi; Zhen-Liang Xu (Chemical Engineering Journal, 2025)

Environmentally-Relevant Concentrations of Atrazine Had Minor Impacts on Gut Microbiota and Liver Metabolite in Juvenile Turtles - Huo-Bin Tang; Xin-Ru Qian; Wan-Qiu Yang; Jia-Meng Yang; Jin-Hui Zhang; Hong-Liang Lu (Archives of Environmental Contamination and Toxicology, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Recent advances in methane and hydrogen production from lignocellulosic degradation with anaerobic fungi - Jinsong Liang; Shiqi Liu; Zhangping Du; Ru Zhang; Longyi Lv; Li Sun; Mohammad Nabi; Guangming Zhang; Panyue Zhang (Bioresource Technology, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Clarifying the impacts of climatic coupling on plastic-mulching potato production in the loess plateau of China - Zhihao He; Kaiyuan Gong; Mengyu Qu; Xiaoya Ru; Shang Chen; Tengcong Jiang; Jing Zhang; Hao Feng; Qiang Yu; Liang He; Jianqiang He (Agricultural Systems, 2024)

Yeast culture enhances long-term fermentation of corn straw by ruminal microbes for volatile fatty acid production: Performance and mechanism - Jinsong Liang; Shiqi Liu; Ru Zhang; Jianning Chang; Longyi Lv; Mohammad Nabi; Guangming Zhang; Panyue Zhang (Journal of Environmental Management, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

The impact of digital technology innovation on green total-factor energy efficiency in China: Does economic development matter? - Ru-Yu Xu; Ke-Liang Wang; Zhuang Miao (Energy Policy, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Exogenous Glutathione Enhances Salt Tolerance in Kenaf by Mediating Modulation of Oxidative Stress Response and DNA Methylation - Shan Cao; Guowang Liang; Lixia Zhang; Jiao Pan; Ru Li; Peng Chen (Journal of Plant Growth Regulation, 2024)

Associations between glycated haemoglobin and multi-modal imaging markers of early cardiac aging - Abigail C. C. Chng; Hong Chang Tan; Louis L. Y. Teo; Ru-San Tan; See Hooi Ewe; Shuang Leng; Xiao-Dan Zhao; Liang Zhong; Woon-Puay Koh; Jean-Paul Kovalik; Fei Gao; Angela S. Koh (GeroScience, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Supramolecular assembly of dual crosslinked nanocomposite polysaccharides hydrogel: Integration of injectable, self-healing, and pH-responsive platform for sustained delivery of polyphenols - Fatima-ezzahra Ettoumi; Hao Huang; Yanqun Xu; Lei Wang; Qiaomei Ru; Yichen Hu; Liang Zou; Zisheng Luo (Food Hydrocolloids, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Astrocyte Activation in the ACC Contributes to Comorbid Anxiety in Chronic Inflammatory Pain and Involves in The Excitation-Inhibition Imbalance - Naixuan Wei; Zi Guo; Mengting Qiu; Ru Ye; Xiaomei Shao; Yi Liang; Boyi Liu; Jianqiao Fang; Junfan Fang; Junying Du (Molecular Neurobiology, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

LECT2 mediates antibacterial immune response induced by Nocardia seriolae infection in the northern snakehead - Jian Teng; Yan Zhao; Yu Bao Li; Liang Yi Xue; Yi Xiang Zhai; Jian Ru Liu; Hui Wang; Xiang Shan Ji (Fish & Shellfish Immunology, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Prediction of acute toxicity for Chlorella vulgaris caused by tire wear particle-derived compounds using quantitative structure-activity relationship models - Jie-Ru Jiang; Wen-Xi Cai; Zhi-Feng Chen; Xiao-Liang Liao; Zongwei Cai (Water Research, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Synthesis and adsorption performance of carboxyl-functionalized magnetic agarose gel microspheres for Cu(II) removal - Mingze Ma; Guanglin Liang; Yi Ru; Jun Chen; Yonghui Zhang; Huifen Weng; Anfeng Xiao; Qiong Xiao (Journal of Environmental Chemical Engineering, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Addition of α-ketoglutaric acid (AKG) reduces deamination in Chinese perch (Siniperca chuatsi) fed with fermented soybean meal as a substitute for fishmeal - Yufei Zhang; Jiacheng Hu; Peisong Lu; Ru Yang; Xu-Fang Liang; Liwei Liu (Fish Physiology and Biochemistry, 2024)

Insights into the influence of polystyrene microplastics on the bio-degradation behavior of tetrabromobisphenol A in soil - Jianning Chang; Jinsong Liang; Yajie Zhang; Ru Zhang; Wei Fang; Haibo Zhang; Su Shiung Lam; Panyue Zhang; Guangming Zhang (Journal of Hazardous Materials, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

One new triterpenoids from Momordica charantia L - Yue Jiang; Bing Liang; Qiong Wu; Jing-Ru Wang; Bing Liu (Natural Product Research, 2024)

Chronic sucralose consumption inhibits farnesoid X receptor signaling and perturbs lipid and cholesterol homeostasis in the mouse livers, potentially by altering gut microbiota functions - Liang Chi; YifeiYang; Xiaoming Bian; Bei Gao; Pengcheng Tu; Hongyu Ru; Kun Lu (Science of The Total Environment, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Interfacial behavior and micro-rheological performance of Pickering emulsions co-stabilized by β-cyclodextrin and xanthan gum - Wei Liang; Fanghui Deng; Yuhang Wang; Wei Yue; Die Hu; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Longitudinal aortic strain, ventriculo-arterial coupling and fatty acid oxidation: novel insights into human cardiovascular aging - Hongzhou Zhang; Shuang Leng; Fei Gao; Jean-Paul Kovalik; Ru-San Tan; Hai Ning Wee; Kee Voon Chua; Jianhong Ching; Xiaodan Zhao; John Allen; Qinghua Wu; Tim Leiner; et al. (GeroScience, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Effect of high corn straw loads on short-chain fatty acid production in semi-continuous rumen reactor - Jinsong Liang; Panyue Zhang; Le Chen; Jianning Chang; Ru Zhang; Guangming Zhang; Yu Tian (Bioresource Technology, 2024)

Design of a tulobuterol patch with improved mechanical properties: effect of transdermal permeation enhancers on the release process of metal ligand-based acrylic pressure-sensitive adhesives - Longyi Nan; Haoyuan Song; Haijun Wang; Ru Mi; Xiaoxu Wang; Liang Fang (Drug Delivery and Translational Research, 2024)

Response of rumen microorganisms to pH during anaerobic hydrolysis and acidogenesis of lignocellulose biomass - Jinsong Liang; Panyue Zhang; Ru Zhang; Jianning Chang; Le Chen; Gongting Wang; Yu Tian; Guangming Zhang (Waste Management, 2024)

Bioconversion of volatile fatty acids from organic wastes to produce high-value products by photosynthetic bacteria: A review - Jinsong Liang; Panyue Zhang; Ru Zhang; Jianning Chang; Le Chen; Guangming Zhang; Aijie Wang (Environmental Research, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Metagenomic insights into the energy metabolism and immune variation of sea cucumber Apostichopus japonicus during reproduction - Beini Deng; Zhaoming Gao; Xiaoshang Ru; Haoyu Tong; Wenke Liang; Igor Eeckhaut; Libin Zhang; Jialei Xu (Aquaculture, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Plastic pollution from takeaway food industry in China - Qian-Qian Zhang; Min-Yi Lan; Hui-Ru Li; Shu-Qing Qiu; Zhao Guo; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Adsorption behaviors and bioavailability of tetrabromobisphenol A in the presence of polystyrene microplastic in soil: Effect of microplastics aging - Jianning Chang; Jinsong Liang; Wei Fang; Haibo Zhang; Yajie Zhang; Hongjun Zhao; Ru Zhang; Panyue Zhang; Guangming Zhang (Environmental Pollution, 2023)

Metagenomic analysis reveals the efficient digestion mechanism of corn stover in Angus bull rumen: Microbial community succession, CAZyme composition and functional gene expression - Jinsong Liang; Jianning Chang; Ru Zhang; Wei Fang; Le Chen; Weifang Ma; Yajie Zhang; Wenjing Yang; Yuehan Li; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Biosorption and biotransformation behaviours of veterinary antibiotics under aerobic livestock wastewater treatment processes - Chih-Hung Chen; Yi-Chu Chiou; Chao-Lung Yang; Jen-Hung Wang; Wan-Ru Chen; Liang-Ming Whang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Targeting STING-mediated pro-inflammatory and pro-fibrotic effects of alveolar macrophages and fibroblasts blunts silicosis caused by silica particles - Liang Ou; Peng Zhang; Zhengpeng Huang; Yuxing Cheng; Qianru Miao; Ru Niu; Yuxin Hu; Ying Chen (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

Impact of National Industrial Relocation Demonstration Zones (NIRDZs) policy on urban carbon emissions in China - Ke-Liang Wang; Ru-Yu Xu; Wei Jiang; Yuan Liu (Environmental Impact Assessment Review, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Rationally designing imidazole-based coordination polymers with high adsorption capacity for removing iodine - Xin Gao; Qing-Hua Hu; Yu-Zhen Shi; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Plasma-treated nano-enabled multimodal coatings made of phototherapeutic molybdenum disulfide and fucoidan prevent catheter-associated urinary tract issues - Jia-Wei Liang; Chia-Hung Liu; Kevin C.-W. Wu; Pei-Ru Jheng; Er-Yuan Chuang (Chemical Engineering Journal, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Environmental regulation, industrial agglomeration, and marine green development efficiency: an empirical analysis from China’s coastal provinces - Ke-Liang Wang; Xiang-Xiang Ru; Li-Li Ding; Yun-He Cheng (Environmental Science and Pollution Research, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Molybdenum carbide changes the abundance of antibiotic resistance genes and bacterial communities in bioelectrocatalytic systems treating wastewater contaminated by tetracycline - Yi Shao; Yu-Xiang Lu; Shi-Ru Gao; Bolun Xie; Xiao-Li Yang; Hai-Liang Song (Bioresource Technology Reports, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Cloning, heterologous expression, and functional characterization of a hydroxyphenylpyruvate reductase (HPPR) gene involved in rosmarinic acid biosynthesis in Prunella vulgaris - Mei Ru; Liuyan Chen; Jiali Liu; Tingting Lan; Chuchu Yang; Xiaoyao Tan; Chuanmei Wu; Pan Liang; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Prodigiosin as an antibiofilm agent against multidrug-resistant Staphylococcus aureus - Jing Yan; Qi Yin; Hao Nie; Jinyou Liang; Xiang-Ru Liu; Yingli Li; Hong Xiao (Biofouling, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Genomic vulnerability to climate change in Quercus acutissima , a dominant tree species in East Asian deciduous forests - Shuai Yuan; Yong Shi; Biao‐Feng Zhou; Yi‐Ye Liang; Xue‐Yan Chen; Qing‐Qing An; Yan‐Ru Fan; Zhao Shen; Pär K. Ingvarsson; Baosheng Wang (Molecular Ecology, 2023)
Understanding the evolutionary processes that shape the landscape of genetic variation and influence the response of species to future climate change is critical for biodiversity conservation. Here, we sampled 27 populations across the distribution range of a dominant forest tree, Quercus acutissima , in East Asia, and applied genome‐wide analyses to track the evolutionary history and predict the fate of populations under future climate. We found two genetic groups (East and West) in Q. acutissima that diverged during Pliocene. We also found a heterogeneous landscape of genomic variation in this species, which may have been shaped by population demography and linked selections. Using genotype‐environment association analyses, we identified climate‐associated SNPs in a diverse set of genes and functional categories, indicating a model of polygenic adaptation in Q. acutissima . We further estimated three genetic offset metrics to quantify genomic vulnerability of this species to climate change due to the complex interplay between local adaptation and migration. We found that marginal populations are under higher risk of local extinction because of future climate change, and may not be able to track suitable habitats to maintain the gene–environment relationships observed under the current climate. We also detected higher reverse genetic offsets in northern China, indicating that genetic variation currently present in the whole range of Q. acutissima may not adapt to future climate conditions in this area. Overall, this study illustrates how evolutionary processes have shaped the landscape of genomic variation, and provides a comprehensive genome‐wide view of climate maladaptation in Q. acutissima .

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

P2Y1R and P2Y2R: potential molecular triggers in muscle regeneration - Min-Jia Wang; Bi-Ru Yang; Xin-Yu Jing; Yao-Zheng Wang; Lu Kang; Kai Ren; Liang Kang (Purinergic Signalling, 2023)
Muscle regeneration is indispensable for skeletal muscle health and daily life when injury, muscular disease, and aging occur. Among the muscle regeneration, muscle stem cells’ (MuSCs) activation, proliferation, and differentiation play a key role in muscle regeneration. Purines bind to its specific receptors during muscle development, which transmit environmental stimuli and play a crucial role of modulator of muscle regeneration. Evidences proved P2R expression during development and regeneration of skeletal muscle, both in human and mouse. In contrast to P2XR, which have been extensively investigated in skeletal muscles, the knowledge of P2YR in this tissue is less comprehensive. This review summarized muscle regeneration via P2Y1R and P2Y2R and speculated that P2Y1R and P2Y2R might be potential molecular triggers for MuSCs’ activation and proliferation via the p-ERK1/2 and PLC pathways, explored their cascade effects on skeletal muscle, and proposed P2Y1/2 receptors as potential pharmacological targets in muscle regeneration, to advance the purinergic signaling within muscle and provide promising strategies for alleviating muscular disease.

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Sipunculus nudus genome provides insights into evolution of spiralian phyla and development - Yi Qi; Liang Chen; Binhua Wu; Xiaoning Tang; Xiao Zhu; Ru Li; Kefeng Wu; Hui Luo (Frontiers in Marine Science, 2023)
Introduction Sipunculus nudus is the most known species in the genus Sipunculus , distributed in tropical and subtropical coastal waters. Methods PacBio sequencing and Illumina sequencing were combined for whole-genome sequencing of S. nudus . LC-MS/MS analysis was performed for the metabolomics of S. nudus . Results Herein, we report a 1.75 Gb complete genome assembly with a contig N50 size of 450 kb of the S. nudus based on a strategy combining third-generation long-read sequencing and Illumina sequencing. A total of 80391 protein-coding genes are annotated in this genome. Furthermore, gene family evolution analysis shows that S. nudus belonged to Mollusca or was close to Mollusca , but distinct with Annelida . Transcriptome analysis indicates the involvement of complex developmental events in larve. KEGG pathway analysis of differentially expressed genes showed that these DEGs were mainly enriched in the pathway of amino acid metabolism, lipid metabolism and transport and catabolism. LC-MS/MS analysis shows that S. nudus was rich in a variety of nutritional and functional components, such as carnitine, free amino acids, unsaturated fatty acids, inosine and methionine sulfoxide. Combined transcriptome with LC-MS/MS analysis, the results showed that gene expression and metabolic level involved in the inosine, arginine and proline biosynthesis of S. nudus during different growth stages were significantly changed. Discussion Our genome assembly provides an important genome resource and new insight into the relationships of Sipuncula to other spiralian phyla. Meanwhile, transcriptome and LC-MS/MS analysis reveal the systematic gene expression profiles and metabolite components of S. nudus during different growth stages, which provide new insight into the exploration and development of bioactive molecules of S. nudus .

Fiscal decentralization, industrial structure upgrading, and carbon emissions: evidence from China - Bin Zhao; Ke-Liang Wang; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Contrasting treeline dynamics of pine and birch in response to climate warming in the Karakoram - Munawar Ali; Shalik Ram Sigdel; Xiangyu Zheng; Fayaz Asad; Ru Huang; Haifeng Zhu; Sher Muhammad; Iqtidar Hussain; Saulat Hussain; J. Julio Camarero; Eryuan Liang (Trees, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Increase in rosmarinic acid accumulation and transcriptional responses of synthetic genes in hairy root cultures of Prunella vulgaris induced by methyl jasmonate - Mei Ru; Yonghua Li; Min Guo; Liuyan Chen; Yong Tan; Liang Peng; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Unexpected climate variability inferred from a 380-year tree-ring earlywood oxygen isotope record in the Karakoram, Northern Pakistan - Haifeng Zhu; Ru Huang; Fayaz Asad; Eryuan Liang; Achim Bräuning; Xuezhen Zhang; Binod Dawadi; Wenmin Man; Jussi Grießinger (Climate Dynamics, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Study on the crustal stress field of the Tengchong volcanic area using composite focal mechanism method - Shu-zhong Sheng; Yong-ge Wan; Chang-sheng Jiang; Xiao-shan Wang; Shan-shan Liang; Gen-ru Xiao; Xiao-hui Hu (Applied Geophysics, 2021)

The gut microbiome and arsenic-induced disease—iAs metabolism in mice - Yifei Yang; Liang Chi; Yunjia Lai; Yun-Chung Hsiao; Hongyu Ru; Kun Lu (Current Environmental Health Reports, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

A Review of Functional Near-Infrared Spectroscopy Studies of Motor and Cognitive Function in Preterm Infants - Quan Wang; Guang-Pu Zhu; Li Yi; Xin-Xin Cui; Hui Wang; Ru-Yi Wei; Bing-Liang Hu (Neuroscience Bulletin, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

A tree-ring–based summer (June–July) minimum temperature reconstruction for the western Kunlun Mountains since AD 1681 - Ru Huang; Haifeng Zhu; Eryuan Liang; Fayaz Asad; Jussi Grießinger (Theoretical and Applied Climatology, 2019)

A tree ring-based winter temperature reconstruction for the southeastern Tibetan Plateau since 1340 CE - Ru Huang; Haifeng Zhu; Eryuan Liang; Bo Liu; Jiangfeng Shi; Ruibo Zhang; Yujiang Yuan; Jussi Grießinger (Climate Dynamics, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Use of discrete choice experiments to facilitate design of effective environmentally friendly agricultural policies - Na-na Wang; Liang-guo Luo; Ya-ru Pan; Xue-mei Ni (Environment, Development and Sustainability, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Gut microbiome disruption altered the biotransformation and liver toxicity of arsenic in mice - Liang Chi; Jingchuan Xue; Pengcheng Tu; Yunjia Lai; Hongyu Ru; Kun Lu (Archives of Toxicology, 2019)

Genome-wide DNA methylation analysis in jejunum of Sus scrofa with intrauterine growth restriction - Yue Hu; Liang Hu; Desheng Gong; Hanlin Lu; Yue Xuan; Ru Wang; De Wu; Daiwen Chen; Keying Zhang; Fei Gao; Lianqiang Che (Molecular Genetics and Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Absorption and subcellular distribution of cadmium in tea plant (Camellia sinensis cv. “Shuchazao”) - De-ju Cao; Xun Yang; Geng Geng; Xiao-chun Wan; Ru-xiao Ma; Qian Zhang; Yue-gan Liang (Environmental Science and Pollution Research, 2018)

Individual susceptibility to arsenic-induced diseases: the role of host genetics, nutritional status, and the gut microbiome - Liang Chi; Bei Gao; Pengcheng Tu; Chih-Wei Liu; Jingchuan Xue; Yunjia Lai; Hongyu Ru; Kun Lu (Mammalian Genome, 2018)

Analysis of three-dimensional endocardial and epicardial strains from cardiac magnetic resonance in healthy subjects and patients with hypertrophic cardiomyopathy - Xiaodan Zhao; Ru San Tan; Hak Chiaw Tang; Shuang Leng; Jun-Mei Zhang; Liang Zhong (Medical & Biological Engineering & Computing, 2018)

Spatial distribution modeling of temperature increase for the uplifted mountain terrains and its characteristics in Southwest China - Yan-xia Wang; Kun Ding; Mao-biao Li; Ru-liang Zhou (Journal of Mountain Science, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Molecular cloning and characterisation of two enzymes involved in the rosmarinic acid biosynthesis pathway of Prunella vulgaris L. - Mei Ru; Kunru Wang; Zhenqing Bai; Liang Peng; Shaoxuan He; Tianlin Pei; Yanyan Jia; Hongyan Li; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Temporal properties of dual-peak responses of mouse retinal ganglion cells and effects of inhibitory pathways - Ru-Jia Yan; Hai-Qing Gong; Pu-Ming Zhang; Shi-Gang He; Pei-Ji Liang (Cognitive Neurodynamics, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

Establishment of Salvia castanea Diels f. tomentosa Stib. hairy root cultures and the promotion of tanshinone accumulation and gene expression with Ag+, methyl jasmonate, and yeast extract elicitation - Bo Li; Bangqing Wang; Hongyan Li; Liang Peng; Mei Ru; Zongsuo Liang; Xijun Yan; Yonghong Zhu (Protoplasma, 2016)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

The Recovery Process of Mice Tracheal Epithelium Injured by 5-FU and Its Microarray Analysis - Jing-Ru Zhang; Nan Song; Xin-Shan Jia; Shan-Liang Sun; Xiao-Bo Ma; En-Hua Wang (Cell Biochemistry and Biophysics, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

Spatial-temporal scales of Green Island wake due to passing of the Kuroshio current - Shih-Jen Huang; Chung-Ru Ho; Sheng-Lin Lin; Shin-Jye Liang (International Journal of Remote Sensing, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Visual pattern discrimination by population retinal ganglion cells’ activities during natural movie stimulation - Ying-Ying Zhang; Ru-Bin Wang; Xiao-Chuan Pan; Hai-Qing Gong; Pei-Ji Liang (Cognitive Neurodynamics, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Spatio-temporal variation of landscape heterogeneity under influence of human activities in Xiamen City of China in recent decade - Yixiong Huang; Xiuqin Yin; Gongfu Ye; Jiemin Lin; Ru Huang; Na Wang; Liang Wang; Yue Sun (Chinese Geographical Science, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Trends of grain yield and plant traits in Chinese maize cultivars from the 1950s to the 2000s - Xiaoke Ci; Mingshun Li; Jiashun Xu; Zhenyu Lu; Pengfei Bai; Gaolin Ru; Xiaoling Liang; Degui Zhang; Xinhai Li; Li Bai; Chuanxiao Xie; Zhuanfang Hao; et al. (Euphytica, 2012)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

Biotreatment of oily wastewater by rhamnolipids in aerated active sludge system - Hong-zi Zhang; Xu-wei Long; Ru-yi Sha; Guo-liang Zhang; Qin Meng (Journal of Zhejiang University-SCIENCE B, 2009)

Nearshore scavenging phenomenon elucidated by 234th/238u disequilibrium in the coastal waters off Western Taiwan - Ching-Ling Wei; Jing-Ru Tsai; Liang-Saw Wen; Su-Cheng Pai; Jen-Hua Tai (Journal of Oceanography, 2009)

Phthalic Acid Induces Oxidative Stress and Alters the Activity of Some Antioxidant Enzymes in Roots of Malus prunifolia - Ru Bai; Fengwang Ma; Dong Liang; Xin Zhao (Journal of Chemical Ecology, 2009)

A curvature-based approach for left ventricular shape analysis from cardiac magnetic resonance imaging - Si Yong Yeo; Liang Zhong; Yi Su; Ru San Tan; Dhanjoo N. Ghista (Medical & Biological Engineering & Computing, 2009)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Therapeutic effect of microencapsulated porcine retinal pigmented epithelial cells transplantation on rat model of Parkinson’s disease - Hou-Liang Zhang; Jian-Jun Wu; Hui-Min Ren; Jian Wang; Ya-Ru Su; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Genetic analysis, molecular tagging and mapping of the thermo-sensitive genic male-sterile gene (wtms1) in wheat - Q. H. Xing; Z. G. Ru; C. J. Zhou; X. Xue; C. Y. Liang; D. E. Yang; D. M. Jin; B. Wang (Theoretical and Applied Genetics, 2003)

Habitat Degradation of Rhinopithecus bieti in Yunnan, China - Wen Xiao; Wei Ding; Liang-Wei Cui; Ru-Liang Zhou; Qi-Kun Zhao (International Journal of Primatology, 2003)

Cloning, characterization and functional expression of a new β- d-fructofuranosidase (Osβfruct2) cDNA from Oryza sativa - Ru-Huei Fu; Yuan-Liang Wang; Hsien-Yi Sung (Biotechnology Letters, 2003)